(untitled) (ASEAN Engineering Journal, 2024)
Water is a very important need for human life. The need for clean water has increased due to changes in people's behavior during the COVID-19 pandemic. Despite the increasing need for clean water during the pandemic, access to it remains unequal. One of the areas with poor water sources is Klumprit Village, Nusawungu, Cilacap, Central Java, where the water is cloudy, yellow in color, and a rustic smell. According to the Regulation of Ministry of Health of the Republic of Indonesia Number 32 of 2017, water that is suitable for sanitation needs is water that is odorless, tasteless, not cloudy or has a low level of turbidity. Ozone is an environmentally friendly technology because it does not produce harmful by-products. In addition to ozone, the production of clean water can use Advanced Oxidation Processes (AOPs) with (O3/H2O2). The existence of H2O2 will increase the ability of ozone in the production of clean water or water purification. In this study, ozonation and AOPs (O3/H2O2) were carried out to purify the yellow and cloudy well water in Klumprit Village, Cilacap, Central Java as an effort to improve public health during the COVID-19 pandemic. The research method was to compare ozonation and AOPs (O3/H2O2). The study will include variations in pH levels, specifically neutral pH (untreated sample) and alkaline, as well as different concentrations of H2O2. The experimental data included Fe and Mn content in water before and after the treatment process. Based on the results of this study, it was found that the yellow color of the groundwater in Klumprit village is caused by high levels of manganese (Mn). The lowest concentration of Mn was achieved after 60 minutes of ozonation at an alkaline pH of 9, with a concentration of 0.266 mg/L. The iron (Fe) content showed fluctuation for both treatment methods, ozonation (O3) and advanced oxidation processes (O3/H2O2).